Connected Mathematics Ability Seen from Student Cognitive Style on STAD – Peer Tutoring Learning Model - Amin, Moh. Saiful Bakhril; Kartono, Kartono; Dewi (Nino Adhi), Nuriana Rachmani (Unnes Journal of Mathematics Education Research, 2020)
Connected mathematics ability of students and students’ cognitive style are important in learning mathematics. This research aims to (1) find out effectiveness of STAD (Student Team Achievement Division) – Peer Tutoring learning model to connected mathematics ability of students, and (2) describe connected mathematics ability of students seen from cognitive style. This research was done for eighth graders of one of Islamic JHS in Cirebon within academic year 2018/2019. This mixed method research with concurent embedded design used observation, cognitive style test, student connected mathematics ability test, and interview as techniques of collecting data. The technique of analyzing data was quantitative data analysis: parametric statistic and descriptive-qualitative analysis technique. The findings showed: (1) STAD-Peer Tutoring was effective to connected mathematics ability of the students; (2) students with Field Independent (FI) cognitive style were able to connect each topic in mathematics, to connect mathematics concept to other discipline of knowledge, and to connect mathematics to daily life based on the given facts. Students with Field Dependent (FD) were able to connect mathematics concept to other diciplines of knowledge and to connect mathematics to daily life.